Single-nucleotide variants and epimutations induce proteasome inhibitor resistance in multiple myeloma - Haertle, Larissa; Barrio, Santiago; Munawar, Umair; Han, Seungbin; Zhou, Xiang; Simicek, Michal; Vogt, Cornelia; Truger, Marietta; Fernandez, Rafael Alonso; Steinhardt, Maximilian; Weingart, Julia Vera; Snaurova, Renata; et al. (Clinical cancer research, 2023)
Proteasome inhibitors (PI) are the backbone of various treatment regimens in multiple myeloma. We recently described the first in-patient point mutations affecting the 20S subunit PSMB5 underlying PI resistance. Notably, in vivo, the incidence of mutations in PSMB5 and other proteasome encoding genes is too low to explain the development of resistance in most of the affected patients. Thus, additional genetic and epigenetic alterations need to be explored.We performed DNA methylation profiling by Deep Bisulfite Sequencing in PSMB5, PSMC2, PSMC5, PSMC6, PSMD1, and PSMD5, a subset of proteasome subunits that have hitherto been associated with PI resistance, recruited from our own previous research, the literature, or a meta-analysis on the frequency of somatic mutations. Methylation was followed up on gene expression level and by dual-luciferase reporter assay. The KMS11 cell line served as a model to functionally test the impact of demethylating agents.We identified PSMD5 promoter hypermethylation and subsequent epigenetic gene silencing in 24% of PI refractory patients. Hypermethylation correlated with decreased expression and the regulatory impact of this region was functionally confirmed. In contrast, patients with newly diagnosed multiple myeloma, along with peripheral blood mononuclear cells and CD138+ plasma cells from healthy donors, generally show unmethylated profiles.Under the selective pressure of PI treatment, multiple myeloma cells acquire methylation of the PSMD5 promoter silencing the PSMD5 gene expression. PSMD5 acts as a key orchestrator of proteasome assembly and its downregulation was described to increase the cell's proteolytic capacity. PSMD5 hypermethylation, therefore, represents a novel mechanism of PI tolerance in multiple myeloma.